Authentic Materials of Choice among English Lecturers - Sunnatul Mufarrohah; Ahmad Munir; Syafi’ul Anam (Linguistic, English Education and Art (LEEA) Journal, 2022)
This study aims to reveal the indicators of lecturers in choosing materials. The method used in this research is descriptive qualitative using a narrative approach. Researchers used documentation, document analysis checklists, and interview guidelines as research instruments. The results of the study indicate that lecturers have four criteria in choosing authentic materials, including 1) authentic materials must follow the needs of students; 2) authentic material must be essential to teach; 3) authentic material must be easy to understand; 4) Authentic materials must be up-to-date. Based on the criteria, several authentic materials can be used: letterforms, order forms, signs, photos, and authentic auditory materials such as videos and songs to provide students with an enlightening and exciting learning experience. In conclusion, English lecturers have used various types of authentic materials such as pictures, videos, and songs using several criteria, such as appropriateness, excitement, understandable, and up-to-date. Keywords: Authentic Material, EFL, Learning, Lecturer